Clinical characteristics of 582 patients with uveal melanoma in China - Liu, Yue Ming; Jonas, Jost B. (PLOS ONE, 2015)
Objective To assess clinical characteristics, treatment and survival of patients with uveal melanoma in China. Methods The retrospective study included all patients with malignant uveal melanoma who were consecutively examined in the study period from January 2005 and June 2015 in the Beijing Tongren hospital. Results The mean age of the 582 patients (295(50.7%) women) was 44.6±12.6 years (range:5-77 years). The tumors were located most often in the superior temporal region (in 117(21.5%) patients) and least common in the inferior region (in 31(5.7%) patients). In 548(94.2%) patients, the tumors were located in the choroid, in 33(5.7%) patients in the ciliary body, and in one (0.2%) patient in the iris. Treatment included episcleral brachytherapy (415(71.3%) patients), local tumor resection (48(8.2%) patients) and primary enucleation (119(20.4%) patients). In 53 individuals out of the 415 patients with primary brachytherapy, episcleral brachytherapy was followed by enucleation, due to an increasing tumor size or due to uncontrolled neovascular glaucoma. Median follow-up time was of 30 months (range: 1-124 months; mean: 34.8 ± 24.4 months). Overall survival rate at 5 and 10 years was of 92.7% and 85.1%. Younger age (P = 0.017), tumor location in the nasal meridian(P = 0.004), smaller tumor size (P<0.001), hemispheric tumor shape (P = 0.025), histological tumor cell type (spindle-cell type versus epitheloid cell type;P = 0.014), and type of treatment (episcleral brachytherapy versus local tumor resection and versus primary enucleation; P<0.001) were significantly associated with the overall survival in univariate analysis, while in multivariate analysis only smaller tumor size was significantly (P<0.001; RR: 4.75; 95% confidence interval:2.11,10.7) associated with better overall survival. Conclusions In this study on clinical characteristics of uveal melanoma of a larger group of patients from China, the onset age was considerably younger and survival rate better than in studies from Western countries. Tumor size was the most significant factor for survival.